Characterization of newly introduced bacterial blight pathogen risk to African rice production and preparedness plans to limit the spread of seed-borne pathogen of high phytosanitary importance - Onaga, O.; Eyokia, M.; Tella, E.O.; Dossou, B.A.; Pinili, D.; Van Schepler, L.; Bachabi, F.; Gouete, M.A.; Zenna, N.; Amoah, N.K.A.; Manneh, B.; Kumar, L. (Africa Rice Center, 2023)
Transboundary spread of pathogens poses a serious risk to crops in the introduced locations. In 2023, bacterial blight (BB) was observed in Uganda for the first time. Genomic DNA was extracted from two BLB-UG cultures and subjected to whole genome sequencing using Illumina NovaSeq (Novogene Inc., Beijing). Genetic analysis of two BB-UG isolates grouped with the BLB isolates of Yunnan province of China termed BB-YN endemic in the southwestern part of China. The 99% similarity between BB strains of China and Uganda suggests the BB-UG isolate detected in Uganda was likely a recent introduction from East Asia. This spread of Asian Strains of BB to Africa poses a serious threat to rice production in the region. PHI AfricaRice team is conducting risk assessment and developing preparedness plans to mitigate the spread of BB and its consequences on rice production in Uganda and Africa.